Can the state make you more religious? Evidence from turkish experience - ÇOKGEZEN, MURAT (My University, 2022)
This paper first evaluates the impact of a two-decade-long Islamization policy carried out by a pro-Islamist party, which came to power in 2002 in Turkey, on the attitudes of Turkish people toward religious values, religious practices, and clergy. In this regard, how the importance of religion, frequency of going to mosques, and trust in the clergy have changed among Turkish Muslims between 2002 and 2018 were examined by using World Values Survey data and employing logistic regression analysis. Estimation results indicated a reduction in belief in God, attendance to mosques, and trust in clergy, which imply the failure of the Islamization policy. Second, we explored what caused the failure by using the same data set and methodology. Our estimations suggested that the symbiotic relationship between the pro-Islamist government and religious clergy and institutions may explain the failure. As the government is identified with religion in the eye of the public, dissatisfaction with the government turned to dissatisfaction with religious values.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Genel Sosyoloji ve Metedoloji; İlahiyat; Social Sciences and Humanities; Sociology; General Sociology and Methodology; Theology; SOSYOLOJİ; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); DİN; Sanat ve Beşeri Bilimler; Sanat ve Beşeri Bilimler (AHCI); SOCIOLOGY; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); RELIGION; ARTS & HUMANITIES; Arts & Humanities (AHCI); General Arts and Humanities; Arts and Humanities (miscellaneous); General Social Sciences; Conservation; Sociology and Political Science; Religious Studies; Social Sciences & Humanities; Islamization; Government intervention to religion; Politicization of religion; Turkey; SECULARIZATION; CONFIDENCE; AKP; PARTICIPATION; INSTITUTIONS; ECONOMICS; FREEDOM; LEADERS; TURKEY; TRENDS